Nitrogen doses on physiological attributes and yield of sugarcane grown under subsurface drip fertigation - Rhein, Andressa Freitas de Lima (2017)
Soil hydric availability and nitrogen fertilization are important environmental factors that influence sugarcane production. In the present study, the physiological attributes SPAD index, maximum photochemical efficiency of photosystem II (Fv/Fm), leaf area index (LAI), chlorophyll and carotenoid content, and sugarcane productivity were assessed under different nitrogen doses (0, 50, 100, 150, and 200 kg N ha−1) applied in the form of urea via subsurface drip fertigation. The physiological attributes were determined 38, 121, 208, 291, and 381 days after the third harvest (DAH), and stalk and sugar productivity at 381 DAH. The 100 kg N ha−1 dose has produced better results for the sugarcane physiological attributes. Increasing doses of nitrogen applied via subsurface drip fertigation increased the productivity of stalks and sugar considerably.